The effect of crude alcoholic extracted for the Seeds and Leaves of Apium graveolens Var dulce. In the level of some female hormones in albino Mice. (Baghdad Science Journal, 2012)
The quantitative determination of the estrogen E2, Progestron P4 & follicle stimulating hormones FSH in the serums of Albino mice used in the experiments & treated by crude alcoholic extracted 95% of the seeds & leaves of Apium graveolens was a significant increase in the concentration of estrogen of different kinds of the extracted in comparison with the values of the coefficient of the control group, that is the study recorded a significant increase of the concentration of estrogen; it was the highest in the mice which was administrated by the methanolic extracted 95%, then it was less in the mouse which was administrated by the ethanolic extracted., and it was the least in the mice which were administrated by the crude ethanolic-methanoloic extracted of the seeds of Apium graveolens; while the increase of the concentration of estrogen of different crude alcoholic extracted leaves of Apium graveolens was the highest than the extracted of the seeds, & it was less concentration in the mice which were administrated by the methanolic extracted 95%, & then it was the least in the mice which were administrated by the crude ethanolic-methanolic extracted leaves of Apium graveolens in comparison with the values of the control group. Further, the plant extracted created a significant increase of the concentration of progestron P4; the statistics analysis recorded that the concentration of progestron was the highest in the mice which were administrated by the methanolic extracted 95%, then it was less in the mice which were administrated by the ethanolic extracted 95%, and the least in the mice which were administrated by the crude ethanolic-methanolic extracted of the seeds of apium graveolens whereas, a significant increase of the concentration of progrstrone was recorded in the leaves of Apium graveolens as follows: it was the highest in the mice which were administrated by the ethanolic extracted 95%, then it was less in the mice which were administrated by the crude methanolic extracted 95%, and it was the least in the mice which were administrated by the crude ethnolic-methanolic extracted in comparison with the coefficient of control group. The study also proved that there was a significant increase of the concentration of the follicle stimulating hormone FSH whose greatest concentration in the mice which was administrated by the crude ethanolic-methanolic for the seeds of Apim graveolens, it was less concentration in the mice which was administrated by crude methanolic extracted 95% of the seeds, and it was the least in the mice which was administrated by the methanolic extracted 95% of the leaves of Apium graveolens in comparison with the concentrations of the coefficient of the control group. While, the results recorded a significant decrease of the FSH in the mice which was administrated by the crude ethanolic extracted of the seeds & leaves of Apium graveolens a highest decrease, it was less concentration in the mice which was administrated by the crude ethanolic-methanolic extracted of the leaves of apium graveolens, in comparison with the concentration in the control group.